2015
DOI: 10.3390/agronomy5020107
|View full text |Cite
|
Sign up to set email alerts
|

Barley Leaf Area and Leaf Growth Rates Are Maximized during the Pre-Anthesis Phase

Abstract: Leaf developmental traits are an important component of crop breeding in small-grain cereals. Surprisingly, little is known about the genetic basis for the differences in barley (Hordeum vulgare L.) leaf development. The two barley row-type classes, i.e., two-and six-rowed, show clear-cut differences in leaf development. To quantify these differences and to measure the genetic component of the phenotypic variance for the leaf developmental differences in both row-type classes we investigated 32 representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
16
0
1
Order By: Relevance
“…QTLs that affect early development are characterized by their influence on SHO and SEL. SEL is strongly related to the phase from awn primordium to tipping, which was shown to be the most decisive developmental phase for spikelet survival ( Alqudah and Schnurbusch, 2014 ) and leaf growth rate ( Alqudah and Schnurbusch, 2015 ) in barley. The length of this phase is therefore assumed to play a key role in determining a plant’s yield potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QTLs that affect early development are characterized by their influence on SHO and SEL. SEL is strongly related to the phase from awn primordium to tipping, which was shown to be the most decisive developmental phase for spikelet survival ( Alqudah and Schnurbusch, 2014 ) and leaf growth rate ( Alqudah and Schnurbusch, 2015 ) in barley. The length of this phase is therefore assumed to play a key role in determining a plant’s yield potential.…”
Section: Resultsmentioning
confidence: 99%
“…This phase is terminated with anthesis resulting in the onset of the grain-filling phase. The length of different preanthesis subphases has been shown to be under genetic control ( Kernich et al , 1997 ; Borras et al , 2009 ; Borras-Gelonch et al , 2010 ; Borras-Gelonch et al , 2012 ; Alqudah et al , 2014 ) and impacts yield-related traits ( Miralles et al , 2000 ; Alqudah and Schnurbusch, 2014, 2015 ). The postanthesis phase is also assumed to have a major impact on yield by determining the time frame for grain-filling ( Evans and Wardlaw, 1976 ; Egli, 2004 ), which controls the yield component grain weight ( Distelfeld et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Barley exists in two morphologically distinct spike forms, referred to as ‘two‐rowed’ and ‘six‐rowed’, which also differ in their leaf blade area (LA) (Alqudah and Schnurbusch, ). To study the natural genetic variation of LA in spring barley, 218 worldwide accessions (125 two‐rowed and 93 six‐rowed, Table S1) under greenhouse conditions (Methods S1) at four developmental stages (Zadoks stage, Z): awn primordium (Z31–33), awn tipping (Z49), heading (Z55) and anther extrusion (Z65) (Zadoks et al ., ; Alqudah and Schnurbusch, ) were analysed. A significant difference ( P ≤ 0.05) in the main culm LA between row‐types, in which six‐rowed forms had significantly larger LA at all developmental stages after awn primordium (AP) (Figure a), was detected.…”
Section: Resultsmentioning
confidence: 99%
“…weight per unit leaf area) has been shown to be associated with increased net photosynthetic capacity ( A max ) and leaf nitrogen (N) (Reich et al ., ). Interestingly, Alqudah and Schnurbusch () found that six‐rowed barley (wide leaf) also had significantly lower LMA than two‐rowed types under different growth conditions, implying that six‐rowed forms may have higher leaf nitrogen (N) than two‐rowed. The observed significant increase of leaf nitrogen (%) during the important pre‐anthesis phase in six‐rowed barleys supported this.…”
Section: Discussionmentioning
confidence: 99%
“…During shoot elongation, which captures the growth period between establishing awn primordia and ear emergence, the leaf growth rate and the potential grain number per area are defined 51,53,58 . An extended shoot elongation phase may thus improve grain yield by increasing leaf size, i.e.…”
Section: Grain Yield Correlations Indicate That Yield Formation Depenmentioning
confidence: 99%